1996
DOI: 10.1063/1.362602
|View full text |Cite
|
Sign up to set email alerts
|

Optical and photoelectrical properties of ReS2 single crystals

Abstract: Optical absorption, photoacoustic spectroscopy and photoconductivity were investigated in ReS2 single crystals in the temperature range 50–300 K. The energy gap (1.55 eV at 80 K) and its temperature dependence, the value of the average phonon energy (17 meV) and the electron phonon coupling parameter (S=2.40) as well as the electron-hole mobility due to lattice scattering were determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 15 publications
3
28
0
Order By: Relevance
“…Along Re chain in this material [15,16]. Angle-dependent Raman scattering measurements of these samples show strong anisotropy in the 214 cm −1 peak intensity with clear twofold symmetry, as seen in recent reports [9,17,18].…”
Section: Methodsmentioning
confidence: 59%
“…Along Re chain in this material [15,16]. Angle-dependent Raman scattering measurements of these samples show strong anisotropy in the 214 cm −1 peak intensity with clear twofold symmetry, as seen in recent reports [9,17,18].…”
Section: Methodsmentioning
confidence: 59%
“…[10] Moreover, the distorted T phase is supposed to induce anisotropic electronic, optical and mechanical properties in ReS 2 . [1,8,11,12] Due to the direct bandgap and anisotropic crystal structure of ReS 2 , it therefore is expected to have a wide the growth respectively (for more details see the Experimental Section; Figure S1 in the Supporting Information). The preference of formation of large-area ReS 2 film on sapphire substrate might be attributed to the weak van der Waals interaction between them.…”
Section: Introductionmentioning
confidence: 99%
“…The triclinic crystal structure of ReS2 leads to polarization dependent optical absorption. [65] The anisotropic absorption coefficient and transient absorption was maximum when the light polarization was parallel to the Re chains, and minimum when perpendicularly polarized. [72] Many-body perturbation theory computations have shown that the lowest-energy bright excitons of distorted 1T ReS2 exhibit a perfect figure-eight shape polarization -which is unusual for hexagonal TMDs.…”
Section: Excitonic and Absorption Propertiesmentioning
confidence: 99%
“…Both the monolayer and bulk ReS2 is a direct gap semiconductor with a bandgap of ~1.55 eV for monolayer and 1.47 for bulk, respectively. [35,65] In ReS2 (i) overlapping of electron wavefunctions from adjacent layers is so weak that a modulation of the interlayer distance cannot renormalize the band structure, implying that…”
Section: Band Structure and Electronic Transportmentioning
confidence: 99%